2014
DOI: 10.1186/1472-6963-14-394
|View full text |Cite
|
Sign up to set email alerts
|

The policy-practice gap: describing discordances between regulation on paper and real-life practices among specialized drug shops in Kenya

Abstract: BackgroundSpecialized drug shops (SDSs) are popular in Sub-Saharan Africa because they provide convenient access to medicines. There is increasing interest in how policymakers can work with them, but little knowledge on how their operation relates to regulatory frameworks. This study sought to describe characteristics and predictors of regulatory practices among SDSs in Kenya.MethodsThe regulatory framework governing the Kenya pharmaceutical sector was mapped, and a list of regulations selected for inclusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…In general, medicines can account for 20–60% of healthcare spending and in many situations, up to 90% of the population purchase them through out‐of‐pocket payments . By law, prescription‐only medicines can only be dispensed with a valid prescription and sales need to be registered in a prescription recording book; however, in practice, retail pharmacies may not implement these requirements . The 2009 Access to Essential Medicines in Kenya report indicates that while medicines are generally affordable to the lowest wage government worker, the majority of Kenyans make less than this wage, indicating that medicines may not be affordable to many .…”
Section: Introductionmentioning
confidence: 99%
“…In general, medicines can account for 20–60% of healthcare spending and in many situations, up to 90% of the population purchase them through out‐of‐pocket payments . By law, prescription‐only medicines can only be dispensed with a valid prescription and sales need to be registered in a prescription recording book; however, in practice, retail pharmacies may not implement these requirements . The 2009 Access to Essential Medicines in Kenya report indicates that while medicines are generally affordable to the lowest wage government worker, the majority of Kenyans make less than this wage, indicating that medicines may not be affordable to many .…”
Section: Introductionmentioning
confidence: 99%
“…Intense competition from chains could also encourage other providers to out regulations to gain a competitive advantage, in "race to the bottom" competition, where quality is compromised. Excessive retail-level competition has been linked to reduced regulatory compliance in Kenya (28). While there was no evidence of market dominance by chains as yet in either country, this may be a future risk, especially in prime business locations where chains are currently concentrated.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, association of dispenser's age, years of dispensing experience and professional qualifications with noncompliance with prescription requirements for antibiotics have been reported [33,34]. A study on regulatory compliance of specialized drug shops in Kenya also found association between pharmacy qualifications and likelihood of regulatory compliance [35]. Meanwhile, findings from U.…”
Section: Key Study Outcomesmentioning
confidence: 99%